Detection of Potential Hazards at Different Phases of Fish and Prawn Processing Plants in Khulna - Nargis, A; Hossain, MA; Parween, S (Bangladesh Journal of Scientific and Industrial Research, 2008)
Frozen fish and prawns occupy the highest rank among the export commodities. Export market of frozen fish/prawn totally depends on the freshness of the commodity. In order to give quality assurance of frozen fish and prawns of Bangladesh, the HACCP system is needed for different mechanisms of processing and consumption. In the present investigation, a total of 10 critical points were identified with farm to processing plants. The identification of potential hazards at different phases (catch and storage at fishing area, transportation, prior to processing, factory hygiene, processing, freezing, packaging, storage and shipment and storage at shipping area) of fish and prawn shrimp processing, and implementation of Hazard Analysis Critical Control Points (HACCP) system in this industry is the only weapon which can increase the demand of fish and prawns of Bangladesh in export market. Key words: Potential hazards, critical control points, HACCP, Fish processing plants DOI: 10.3329.bjsir.v43i1.864 Bangladesh J. Sci. Ind. Res. 43(1),131-138, 2008